A rare case of uterine lipo-leiomyoma in a 63-year-old Nigerian woman; a case report - Taiwo Solaja; John Nwadiokwu; Victor Okebalama; Olutomiwa Omokore; Obinna Monday; Ayodeji Ayeni; Harrison Duru; Uchechukwu Nwudele (Babcock University Medical Journal, 2023)
Background: Lipo-leiomyoma accounts for about 0.03%-0.2% of uterine tumours. The aetiology of lipo-leiomyoma is unclear, with some suggesting fatty metamorphogenesis and others involving growth factors and oestrogens. Radiological evaluation and histology are necessary for definitive diagnosis. If asymptomatic, no treatment is needed, but surgical resection is performed in symptomatic patients.